Library Users’ Perceptions of Social Inclusion-Based Library Programs in the West Sumatra Provincial Archives and Library Service - Nia Ramadhani; Marlini Marlini (Darul Yasin Al Sys, 2026)
Social inclusion-based library programs have been developed to strengthen libraries as spaces for learning, community empowerment, and equitable information access. However, their implementation continues to face challenges related to promotion, information dissemination, program continuity, and user participation, making evaluation from users’ perspectives essential. This study aimed to describe users’ perceptions of the social inclusion-based library program implemented at the Regional Archives and Library Office of West Sumatra Province. A quantitative approach with a descriptive method was employed. The study population consisted of 474 library users, from whom 87 respondents were selected through simple random sampling. Data were collected through observation, interviews, and Likert-scale questionnaires and were analyzed using descriptive statistics through mean and grand mean calculations. The findings revealed that users’ perceptions of the program were categorized as good, with an overall mean score of 3.16. The collection indicator obtained a mean score of 2.96, physical accessibility 3.21, marketing 3.16, partnership 3.18, program implementation 3.24, and training 3.26. These results indicate that the program positively supports information access, service accessibility, activity communication, collaborative engagement, program implementation, and users’ skills development. The study concludes that social inclusion-based library programs contribute positively to expanding learning opportunities and supporting community empowerment. These findings contribute to the literature on inclusive library services and provide practical implications for strengthening collection development, promotional strategies, partnerships, and service quality to improve the effectiveness and sustainability of social inclusion-based library programs.